Designing Cognitive Cities - Portmann, Edy.; Tabacchi, Marco E.; Seising, Rudolf; Habenstein, Astrid; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book illustrates various aspects and dimensions of cognitive cities. Following a comprehensive introduction, the first part of the book explores conceptual considerations for the design of cognitive cities, while the second part focuses on concrete applications. The contributions provide an overview of the wide diversity of cognitive city conceptualizations and help readers to better understand why it is important to think about the design of our cities. The book adopts a transdisciplinary approach since the cognitive city concept can only be achieved through cooperation across different academic disciplines (e.g., economics, computer science, mathematics) and between research and practice. More and more people live in a growing number of ever-larger cities. As such, it is important to reflect on how cities need to be designed to provide their inhabitants with the means and resources for a good life. The cognitive city is an emerging, innovative approach to address thisneed.
Cognitive Cities: An Approach from Citizens -- Possibilities for Linguistic Summaries in Cognitive Cities -- An Exploration of Creative Reasoning -- Using Fuzzy Cognitive Maps to Arouse Learning Processes in Cities -- The Role of Interpretable Fuzzy Systems in Designing Cognitive Cities -- Towards Cognitive Cities in the Energy Domain -- A Dynamic Route Planning Prototype for Cognitive Cities.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence